Patterns of Mycoplasma bovis antibodies in cows and calves in Swedish dairy herds, and testing strategies to detect seropositive herds - Hurri E; Compton CWR; Alvåsen K; Tråvén M (Elsevier Inc on behalf of the American Dairy Science Association®, 2025)
Mycoplasma bovis causes severe diseases among cattle. Sweden has a favorable situation for control of this disease, with a low prevalence of M. bovis infected and seropositive herds detected only in the southern parts of the country. To prevent the spread of the infection, analyzing antibody levels is a cost-effective method to determine herd pathogen exposure status. In this study, our aims were to monitor the antibody dynamics in infected herds over time using IDvet ELISA, to both evaluate risk-based sampling and investigate the effect of M. bovis exposure on health and production. We visited and sampled 35 dairy herds, 31 of which were sampled at least 2 times and 26 sampled 4 times and followed for 2 yr. The patterns of herd seroprevalence varied depending on the status before the herd's entry into the study and remained relatively stable at the herd level, although antibody status could differ among age groups. Overall, herds with high exposure prevalence (75%–100% positive cows, n = 13/26), and herds with low exposure prevalence (<25% positive cows, n = 5/26), maintained their exposure status throughout the study. The changes in status observed within the herds, both among calves and cows, included transitions from positive to negative, as well as from negative to positive. In 5 herds, the calf group transitioned from positive to negative, while in 1 herd, the reverse occurred. Three herds exhibited an increase in antibody levels; in 2 of these herds, the cows transitioned from negative to positive, and in 1 herd with positive cows, the calves shifted from negative to positive. A cost-effective test strategy to find likely infected herds involved sampling bulk tank milk and cows with a high SCC, which gave a 90% probability of locating infected herds by the second sampling. Milk production was reduced by 404 kg (1.3 L/d, P = 0.012) in cows positive for M. bovis antibodies. Therefore, controlling the spread of M. bovis infection will likely have a positive effect on reducing income loss for dairy herds in Sweden.
Keywords: cattle; longitudinal; serology; Mycoplasmopsis bovis